Photodegradation of organic pollutants RhB dye using UV simulated sunlight on ceria based TiO2 nanomaterials for antibacterial applications - Kasinathan, Kaviyarasu; Kennedy, John; Elayaperumal, Manikandan; Henini, Mohamed; Malik, Maaza (Nature Publishing Group, 2016)
To photo-catalytically degrade RhB dye using solar irradiation, CeO2 doped TiO2 nanocomposites were synthesized hydrothermally at 700 °C for 9 hrs. All emission spectra showed a prominent band centered at 442 nm that was attributed to oxygen related defects in the CeO2-TiO2 nanocrystals. Two sharp absorption bands at 1418 cm−1 and 3323 cm−1 were attributed to the deformation and stretching vibration, and bending vibration of the OH group of water physisorbed to TiO2, respectively. The photocatalytic activities of Ce-TiO2 nanocrystals were investigated through the degradation of RhB under UV and UV+ visible light over a period of 8 hrs. After 8 hrs, the most intense absorption peak at 579 nm disappeared under the highest photocatalytic activity and 99.89% of RhB degraded under solar irradiation. Visible light-activated TiO2 could be prepared from metal-ion incorporation, reduction of TiO2, non-metal doping or sensitizing of TiO2 using dyes. Studying the antibacterial activity of Ce-TiO2 nanocrystals against E. coli revealed significant activity when 10 μg was used, suggesting that it can be used as an antibacterial agent. Its effectiveness is likely related to its strong oxidation activity and superhydrophilicity. This study also discusses the mechanism of heterogeneous photocatalysis in the presence of TiO2.